Support-controlled chemoselective olefin-imine addition photocatalyzed by cadmium sulfide on a zinc sulfide carrier. - Heinemann, Frank Wilhelm; et al. (Photochemical & Photobiological Sciences, 2007)
The semiconductor catalyzed photoaddition of cyclopentene or cyclohexene to various novel electron-poor imines of type p-XC(6)H(4)(CN)C[double bond, length as m-dash]N(COPh) (X = H, F, Cl, Br, Me, MeO) was investigated as a function of the nature of the cadmium sulfide photocatalyst. Irradiation (lambda>/= 350 nm) of silica supported cadmium sulfide surprisingly did not afford the expected olefin-imine adducts but an imine hydrocyanation product via an unprecedented dark reaction. However, when silica was replaced by zinc sulfide as the support for cadmium sulfide, the expected homoallylic N-benzoyl-alpha-amino cyanides were isolated in yields of 65-84%. Thus, chemoselectivity is introduced through replacing an insulating by a semiconducting support, a hitherto unknown effect in semiconductor photocatalysis. From the sign of the time resolved photovoltage it is found that the mixed metal sulfide interface CdS/ZnS increases the lifetime of photogenerated electron-hole pairs by about one order of magnitude as compared to the SiO(2)/CdS system. The reaction rate increases with increasing imine sigma-Hammett constants and decreasing stability of intermediate benzyl radicals.